Where are the women? A review and conceptual framework for addressing gender equity in charcoal value chains in Sub-Saharan Africa - Ihalainen, Markus; Schure, J.; Sola, P. (Elsevier, 2020)
The importance of the charcoal sector is growing rapidly in Sub-Saharan Africa. In addition to providing an affordable energy source for residents in the continent's growing urban centers, the charcoal value chain offers a critical income source for millions of people. Despite recent studies suggesting that women are taking on an increasing role in charcoal value chains, data and analysis on the role of women and the influence of gendered power relations in the often male-coded charcoal value chain have remained limited. This literature review interrogates the gender dynamics of participation and benefits across charcoal value chains in Sub-Saharan Africa. We find significant support for women's participation throughout value chains, thereby contrasting conventional views of charcoal as a male activity. However, while dynamics change between different contexts, women's participation tends to be significantly higher in retail, while women tend to constitute a minority in other parts of the value chain – often joining the sector in the absence of alternative livelihood opportunities. The review also finds that gender differences exist across various nodes in terms of the scope, nature and outcomes of participation. While significant regional differences exist, our study finds that participation and outcomes tend to generally be influenced by gender differences and inequalities in: 1) access to and control over productive resources and income; 2) social and political capital, and; 3) gender roles and responsibilities. Importantly, other axes of social differentiation, such as generation, marital status, wealth and social class, often intersect with gender relations in influencing outcomes. In addition to structuring the extent, nature and outcomes of women and men's participation, we argue that gender roles and relations may significantly influence the efficiency and sustainability of the charcoal value chain. Based on our findings, we call for placing gender at the core – rather than periphery – of charcoal value chain studies, and propose a conceptual framework for incorporating gender analysis in future value chain studies in the charcoal sector.